2020
DOI: 10.1111/vcp.12883
|View full text |Cite
|
Sign up to set email alerts
|

Reference intervals for serum amyloid A, haptoglobin, ceruloplasmin, and fibrinogen in apparently healthy neonatal lambs

Abstract: Background: Acute-phase proteins (APPs) are considered biomarkers for diagnoses, prognoses, and treatment and health status monitoring. Reference intervals (RIs) are an integral part of diagnostic laboratory testing and clinical decision-making. The RIs for neonatal lambs are lacking. Objective: This study aimed to determine the RIs of serum amyloid A (SAA), haptoglobin (Hp), ceruloplasmin (Cp), and fibrinogen (Fb) concentrations in neonatal crossbred Kivircik lambs. Methods: The study consisted of 42 neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
4
7
0
Order By: Relevance
“…Another study reported that serum SAA concentration increased from the first day of life to the fifth day, the highest level was on the day after birth and then decreased until the second week of life (Kilpi, 2015). In some studies which were conducted on sheep and goats, the researchers found that the SAA and Hp concentrations in healthy animals were quite low in the APP examination (Iliev and Georgieva, 2018;Dinler et al 2020). Similarly in our study, SAA and Hp concentrations of post-treatment and control groups were lower than the concentrations of pre-treatment.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Another study reported that serum SAA concentration increased from the first day of life to the fifth day, the highest level was on the day after birth and then decreased until the second week of life (Kilpi, 2015). In some studies which were conducted on sheep and goats, the researchers found that the SAA and Hp concentrations in healthy animals were quite low in the APP examination (Iliev and Georgieva, 2018;Dinler et al 2020). Similarly in our study, SAA and Hp concentrations of post-treatment and control groups were lower than the concentrations of pre-treatment.…”
Section: Resultssupporting
confidence: 76%
“…Also, the fact that SAA and Hp concentrations were in close values to each other in control and post-treatment groups is another indicator of the success of the treatment. To conclude, the fact that SAA and Hp concentrations were found to be low in healthy animals in some studies (Iliev and Georgieva, 2018;Dinler et al 2020) supports the hypothesis.…”
Section: Resultssupporting
confidence: 52%
“…How general are these findings? Perinatal levels of acute phase proteins have been observed to be low in several species of mammal, for instance rabbits, humans and sheep (Baker and Long, 1990;Kanakoudi et al, 1995;Rygg et al, 1996;Liberatori et al, 1997;Mcnamara and Alcorn, 2002;Mithal et al, 2017;Dinler et al, 2020), but to our knowledge this is the first evidence of a similar trend in a Carnivoran. The unique feature in grey and potentially other phocid seals is that this applies where protection against infection by antibodies may be initially non-existent and then minimal until parental care and lactational support ceases.…”
Section: Acute Phase Proteins-paucity In Pupsmentioning
confidence: 79%
“…The concentrations of different APP change during the first few weeks of ruminant life and are termed age-related changes in APP. In lambs and goat kids, SAA concentrations increase during the first week of life, start to decrease during the second week, and then stabilize at the end of the third week (Eckersall et al, 2008;Ulutas et al, 2017;Niine et al, 2018a;Peetsalu et al, 2019;Dinler et al, 2020). It has been suggested that colostrum intake influences the APP concentration in calves, as their SAA concentrations were found to be low before colostrum consumption and then increased during the first 24 h after birth (Orro et al, 2008;Tóthová et al, 2015).…”
Section: Introductionmentioning
confidence: 99%